Optimalisasi E-Commerce: Rekomendasi Terkomputerisasi Dan Keputusan Pelanggan Melalui Metode SUS - Julius Jerry Nolasco; Binastya Anggara Sekti (Ikatan Ahli Informatika Indonesia, 2024)
The focus of this study is on the development of strategies to optimize E-Commerce performance by enhancing information systems. It highlights recommendation methods, automated calculations, and customer decision-making using the System Usability Scale (SUS) technique. The main objective is to improve the recommendation system, increase information management efficiency, and enhance user satisfaction within an E-Commerce setting. The methods employed include creating a recommendation system based on a product information management model utilizing the K-means algorithm, implementing technology suitability models in accounting information systems, and assessing with a hybrid SUS. Data collection will be crucial in supporting the research's goals. The findings will pinpoint areas for enhancing product recommendation relevance, showcasing user satisfaction, and displaying decision-making effectiveness on the E-Commerce platform. The conclusion stresses the significance of technological integration in shaping the E-Commerce business model and its potential to enrich the online shopping experience. The research proposes that novel marketing strategies in the digital economy era can heighten the competitiveness of E-Commerce companies. This investigation makes a substantial contribution to comprehending and crafting efficient E-Commerce information systems, with vital implications for enhancing business performance and delivering customer value in an ever-changing digital landscape.